Effects of unexpected event urgency and flight scenario familiarity on pilot trainees performance and stress responses - Peng, Xing; Niu, Qingfei; Liang, Yaowei; Luo, Yuchuan; Lu, Ning; Li, Xiuyi (Frontiers in Physiology, 2025)
Pilot trainees’ ability to manage unexpected events is crucial for aviation safety, yet the impact of event urgency and flight scenario familiarity on pilot performance remains under-explored. This study investigates how different urgency levels of unexpected events influence pilot trainees’ flight performance, heart rate, and anxiety in both familiar (single-engine) and less familiar (twin-engine) flight scenarios. Two controlled experiments were conducted using flight simulators: Experiment 1 involved 27 pilot trainees operating a Cessna 172 single-engine simulator under low-urgency and high-urgency conditions, while Experiment 2 involved 25 pilot trainees using a FTD D40/D42 twin-engine simulator, introducing an additional no-event baseline. In the single-engine flight scenario, high-urgency unexpected events significantly impaired pilot trainees’ performance (Cohen’d = 0.454) and increased anxiety (ηp2 = 0.229). In the twin-engine flight scenario, high-urgency unexpected events significantly impaired flight performance (MEI increased, ηp2 = 0.737), elevated heart rate (ηp2 = 0.516), and increased anxiety levels (ηp2 = 0.442) compared to low-urgency events, which had minimal effects and, in some cases, improved pilot trainees focus. Additionally, pilot trainees performed better and exhibited lower anxiety in familiar scenarios, suggesting that task familiarity mitigates the negative impact of high-urgency unexpected events. These findings highlight the importance of incorporating urgency-based training scenarios and cross-aircraft training to enhance pilot trainees’ adaptive responses to unexpected events, ultimately improving flight safety.